Effectiveness of Digital Flipped Learning Evidence-Based Practice on Nurses’ Knowledge, Attitude, and Practice: A Quasi-Experimental Trial - Chao, Wen-Yi; Huang, Li-Chi; Hung, Hung-Chang; Hung, Shih-Chang; Chuang, Tzung-Fang; Yeh, Li-Yueh; Tseng, Hui-Chen (Healthcare (Basel), 2022)
Background: Evidence-based care has become critical in raising the quality of medical facilities. The implementation of evidence-based practice helps medical practitioners make better clinical decisions. Objective: The objective of this study was to investigate whether the innovative flipped teaching model could be as effective as the conventional teaching model in terms of knowledge, attitude, and practice and to confirm the continuous effect. Design: A quasi-experimental design using the flipped and conventional learning groups concurrently with repeat measurements was used. Setting: The setting was a 475-bed regional teaching hospital in Taiwan, from March to July 2020. Participants: The study included 114 licensed nurses who had worked longer than three months, with 57 participants each in two groups. Methods: The participants were assigned to two groups using a block randomization method. All participants completed questionnaires related to knowledge, attitude, and practice of EBP at four-time points: pre-test (T0) and immediately after intervention (T1), at month 1 (T2), and at month 3 (T3). Analysis of repeated generalized estimating equations was used. Results: The flipped and conventional learning groups had significant differences in knowledge, attitude, and practice at the T0 and T1 (p < 0.05). The flipped group was higher than the conventional group at T3 in the knowledge score (p = 0.001) and lower than the conventional group at T2 in the attitude score (p = 0.010). There were no significant differences between the two groups’ practice scores at different time points. There were no significantly different score changes for knowledge, attitude, and practice (p > 0.05). The interaction term only at T3 vs. T0 in the knowledge score was slightly different (p = 0.049) in primary outcome. Conclusion: The intervention methods of both groups were effective. Flipped learning is more flexible and has more time for discussion, which nurses favor. Under the policy promoted in the hospital, EBP combined with the nursing advancement system was standardized, and conventional learning also improved the learning effect.